The relationship between social support and employment anxiety in preschool teacher trainees in China: the mediating role of psychological capital and the moderating role of professional identity - Li, Li; Wang, Guanghua; Zhang, Meng (Frontiers in Psychology, 2025)
IntroductionAgainst the backdrop of a continuously declining birth rate in China, pre-school teacher trainees are facing severe employment challenges and have experienced problems such as employment anxiety. Effective social support, positive psychological capital, and a high level of professional identity can act as a buffer against employment anxiety, alleviating the negative impact of the tense job market on employment anxiety.MethodsThis study recruited 1195 students majoring in preschool education from Years 1 to 4 at four applied-oriented undergraduate institutions in Shanghai, China. The aim was to explore the influence of social support on the employment anxiety of preschool teacher trainees, and to analyze the mechanism of professional identity and psychological capital.These findings carry important theoretical and practical implications for alleviating preschool teacher trainees’ employment anxiety and enhancing their employment quality.ResultsResearch shows that (1) There are some significant differences in social support, psychological capital, employment anxiety and professional identity in terms of gender, grade and major choice; (2) social support negatively predicts employment anxiety; (3) psychological capital partially mediates the link between social support and employment anxiety; (4) professional identity significantly moderates the relationship between psychological capital and employment anxiety.DiscussionThese findings carry important theoretical and practical implications for alleviating preschool teacher trainees’ employment anxiety and enhancing their employment quality.